Physiology-based kinetic modeling of neuronal energy metabolism unravels the molecular basis of NAD(P)H fluorescence transients: $hNikolaus Berndt, Oliver Kann and Hermann-Georg Holzhütter - Berndt, Nikolaus; Kann, Oliver; Holzhütter, Hermann-Georg (Journal of cerebral blood flow & metabolism, 2015)
Imaging of the cellular fluorescence of the reduced form of nicotinamide adenine dinucleotide (phosphate) (NAD(P)H) is one of the few metabolic readouts that en...
Gesehen am 22.05.2020